Risco de quedas em idosos institucionalizados: um estudo descritivo correlacional - Batista, Wagner Oliveira; Pereira, Fabio Dutra; Santana, Rosimere Ferreira; Silva, Luis Aureliano Imbiriba; Gurgel, Jonas Lirio; Alves Junior, Edmundo de Drummond (Online Brazilian Journal of Nursing, 2012)
Objective: To describe and analyze the association between institutionalization time in Long-Term Care Institutions for the Elderly (LTCI) and the balance and risk of falls of this population. Methods: This is a descriptive correlational study. The dependent variables will be measured through the use of scales of balance and stabilometry. The census consists of all population institutionalized at LTCIs in the city of Três Rios (RJ), between September 2011 and March 2012. Data processing includes the Kolmogorov-Smirnov test to verify the distribution. The data presented will be submitted to a Pearson correlation test and the analysis of variance for one factor, to allow comparisons between inter-groups and intra-subgroups. In the event that a Gaussian distribution is not presented, non-parametric tests will be used. The significance level used will be 5%. For statistical analysis BioEstat 5.0 software will be adopted